Racial sovereignty. (September 2020) - Nisancioglu, Kerem
This article explores how International Relations (IR) might better conceptualise and analyse an underexplored but constitutive relationship between race and sovereignty. I begin with a critical analysis of the 'orthodox account' of sovereignty which, I argue, produces an analytical and historical separation of race and sovereignty by: (1) abstracting from histories of colonial dispossession; (2) treating racism as a resolved issue in IR. Against the orthodox account, I develop the idea of 'racial sovereignty' as a mode of analysis which can: (1) overcome the historical abstractions in the orthodox account; (2) disclose the ongoing significance of racism in international politics. I make this argument in three moves. Firstly, I present a history of the 17th century struggle between 'settlers' and 'natives' over the colonisation of Virginia. This history, I argue, discloses the centrality of dispossession and racialisation in the attendant attempts of English settlers to establish sovereignty in the Americas. Secondly, by engaging with criticisms of 'recognition' found in the anticolonial tradition, I argue that the Virginian experience is not simply of historical interest or localised importance but helps us better understand racism as ongoing and structural. I then demonstrate how contemporary assertions of sovereignty in the context of Brexit disclose a set of otherwise concealed colonial and racialised relations. I conclude with the claim that interrogations of racial sovereignty are not solely of historical interest but are of political significance for our understanding of the world today.